We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
146
4
avatar+143 

The sum of a certain infinite geometric series is 2. The sum of the squares of all the terms is 3. Find the common ratio.

 Jan 31, 2019

Best Answer 

 #4
avatar+7477 
+3

That means {\(\dfrac{a}{1-r} = 2\\ \dfrac{a^2}{1-r^2} = 3\).

\(\dfrac{2a}{1+r} = 3\\ \dfrac{2(2-2r)}{1+r} = 3\\ 4-4r = 3+3r\\ 7r = 1\\ r = \dfrac{1}{7}\\ \dfrac{2a}{\frac{8}{7}} = 3\\ 7a = 12\\ a =\dfrac{12}{7}\\\)

So \((r,a) = \left(\dfrac{1}{7},\dfrac{12}{7}\right)\)

.
 Feb 1, 2019
 #1
avatar+280 
+3

The formula for the sum of an infinite geometric sequence is a/1-r

 

1. Take that formula and make an equation from the problem.

 

"The sum of a certain infinite geometric series is 2"

 

So 2=a/1-r               (where r represents common ratio and a represents the first term

 

Then make another equation for the second part of the problem

 

"The sum of the squares of all the terms is 3"

 

So 3=(a^2)/1-(r^2)

 

this is true because when all the terms are squared, the common ratio is also squared.

 

2. Solve for the equations

 

Since we are trying to find the common ratio, solve for r.

 

We get 1/7 as the answer

 

Im not sure if this correct, will someone please check this, I hope this is not a bogus solution!

 Jan 31, 2019
 #3
avatar
+2

You have to set up 2 simultaneous equations as follows:

3=F^2 / (1 - r^2), 2 = F / (1 - r), solve for r, F

This gives r =1/7 and F =12/7

Guest Feb 1, 2019
 #2
avatar
+1

YES!. It is correct. The common ratio is 1/7 and the first term 1 5/7 which all sum up to 2. And their squares sum up to 3. Here are the first 10 terms:

(1.714285714, 0.2448979592, 0.03498542274, 0.004997917534, 0.0007139882192, 0.000101998317, 0.00001457118815, 0.000002081598307, 0.000000297371186 7, 0.000000042481598 1, 0.000000006068799 728)

 Jan 31, 2019
 #4
avatar+7477 
+3
Best Answer

That means {\(\dfrac{a}{1-r} = 2\\ \dfrac{a^2}{1-r^2} = 3\).

\(\dfrac{2a}{1+r} = 3\\ \dfrac{2(2-2r)}{1+r} = 3\\ 4-4r = 3+3r\\ 7r = 1\\ r = \dfrac{1}{7}\\ \dfrac{2a}{\frac{8}{7}} = 3\\ 7a = 12\\ a =\dfrac{12}{7}\\\)

So \((r,a) = \left(\dfrac{1}{7},\dfrac{12}{7}\right)\)

MaxWong Feb 1, 2019

9 Online Users

avatar
avatar